Frontispiece: Exploring the Symmetry, Structure, and Self‐Assembly Mechanism of a Gigantic Seven‐Fold Symmetric Pd84 Wheel. Issue 38 (15th September 2014) - Scullion, Rachel A.; Surman, Andrew J.; Xu, Feng; Mathieson, Jennifer S.; Long, De‐Liang; Haso, Fadi; Liu, Tianbo; Cronin, Leroy
<x xml:space="preserve">Abstract</x> Polyoxometalates In their Communication on page 10032 ff., L. Cronin et al. investigate the self‐assembly of a Pd84 wheel from Pd6− using electrophoresis, size‐exclusion chromatography, and mass spectrometry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>